Anaesthetic Management for Patient with Trigeminal Neuralgia underwent Microvascular Decompression (MVD) - Hardian, Rapto; Pratama, Edwin; Tarigan, Dwi Septwo Rustaminta; Sikumbang, Kenanga Marwan (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Trigeminal neuralgia (TN) is a chronic pain with repeated brief episodes of electric shock-like pain affecting the fifth cranial nerve. Microvascular decompression (MVD) is one of treatments for TN. Anesthetic management for MVD requires special consideration to reduce brain volume (slack brain) and optimise Mean Arterial Pressure (MAP). Female 29-yo, 40kgbw with chief complaint: throbbing pain and intermittent stiffness in right facial area since 1 year ago. Brain MRI examination showed crossing of right superior cerebellar artery (RSCA) branch with right trigeminal nerve near the root entry zone and underwent MVD. Anesthesia using smooth intubation technique and maintenance using a combination of inhalational anaesthetics (sevoflurane 1 vol%) and intravenously (propofol 100mcg/kg/minute, remifentanil 0.2mcg/kgbw/min, and rocuronium 10mcg/kgbw/min). Target for MAP (90mmHg) and EtCO2 (30mmHg). We didn't use mannitol for slack brain. Early emergence with smooth extubation to prevent sudden haemodynamic changes and minimising coughing then for early neurological detection of intracranial complications.The combined use of sevoflurane 1MAC and continuous propofol provides optimal visualisation of the operating area. This combination reduces cerebral blood flow which makes the brain slack and keeps MAP optimal to maintain cerebral perfusion pressure and reduce the risk of cerebral ischemia. The combination of these agents also makes early recovery for more rapid neurological assessments. Anaesthesia management for MVD uses neuroanesthesia principles, balanced anaesthesia, and strict haemodynamic monitoring. The combination of inhalation anaesthetic sevoflurane and intravenous propofol gave optimise visualisation in the operation area and the patient's recovery can be enhanced